USING VIDEOCAPTIONING BASED ACTIVITIES TO DEVELOP EFL SECONDARY SCHOOL LEARNERS’ VOCABULARY - Ika Diar Marthafany Marthafany (Faculty of Teaching and Education, University of August 17, 1945, Banyuwangi, 2023)
This research was conducted to investigate how video captioning based activities help students improve their vocabulary achievement. Video captioning was used to help learners locate textual definitions and pictorial aids to better comprehend the meaning of new words. This research employs classroom action research which has four stages: planning, implementation; observation; reflection. 13 (6 females and 7 males) students participated in this study The observation checklist was used to know students’ engagement during the teaching and learning of vocabulary through video captioning. Meanwhile, the vocabulary test was used to know the students’ vocabulary improvement. All collected data from vocabulary test was quantitatively calculated. Findigs of the study showed that students vocabulary achievement improved from vocabulary test 1 (68), vocabulary test 2 (72), vocabulary test 3 (84), and vocabulary test 4 (88). The findings of the study also showed that the use of video captioning in learning vocabulary could engage students in more meaningful learning environment. Overall, the results of the vocabulary test show that video captioning can increase students' vocabulary. The results of the study also show that student participation and activity have increased. This study shows the benefits of using video captioning to increase students' vocabulary. Video captioning can facilitate students to know unfamiliar words and can encourage them to learn new words more efficiently.